Analisis Pelanggaran Prinsip Kesantunan Dan Penggunaan Strategi Kesantunan Dalam Tindak Tutur Anjuran Pada Reality Show “Terrace House: Opening New Doors” - Getaya, Andardisha; Hapsari, Eky Kusuma; Hamdi, Muhammad Ali (KIRYOKU, 2024)
This study aims to examine the violations of politeness principles in recommending speech acts that occur in the reality show "Terrace House: Opening New Doors". Based on politeness theory proposed by Leech and the politeness strategies from Brown and Levinson, the researcher analyzes data from dialogues containing recommending speech acts delivered by participants in the reality show "Terrace House: Opening New Doors". The research method used is descriptive qualitative with data collection techniques through observation and recording of dialogues containing recommending speech acts. The analysis method used is the referential matching method with recommending speech acts as the determining reference. The results of the study show that there are 48 violations of politeness principles in recommending speech acts. The most frequent violations occur in agreement maxim with 30 instances (63%), followed by violations of appreciation maxim with 11 instances (22%), and violations sympathy maxim with 7 instances (15%). The most frequently used politeness strategy is negative politeness strategy with 17 instances (35%), followed by bald on-record strategy with 14 instances (29%), positive politeness strategy with 10 instances (21%), and off-record strategy with 7 instances (15%). In conclusion, violations of politeness principles often occur in the delivery of recommendations, especially violations of agreement maxim. These violations caused by a lack of understanding of the interlocutor's situation and prioritizing effectiveness over politeness. The negative politeness strategy is the most used strategy to address violations of the agreement maxim, as it helps reduce discomfort and minimizes threats to negative face of the interlocutor.